Chronic Uterine Inversio due to Myoma Geburt - Bobby Indra Utama, SpOG(K) (Universitas Andalas, 2020)
Background: Uterine inversion is a rare obstetric emergency but potentially serious complication of labour. This disease characterized by severe pain and can cause life threatening condition. If these not immediately identified, the massive and underestimated blood loss can lead to hypovolemic shock. There for, early diagnosis and management of this condition is desirable.Objective: Report on the management of chronic uterine inversion due to myoma geburtMethods: Case reportCase: A 46 years old patient was admitted to the gynaecology ward of Dr. M. Djamil Central General hospital with slight bleeding from vagina since 1 month ago with 2-3 pieces of underware dark-red colored, with pain. Bleeding from the vagina often recurs. There was a mass revealed from vagina with size as big as baby’s head. The mass had pus and necrotic tissue.Conclusion: Uterine inversion is an serious obstetric complication due to life threaten of the patient. Its low incidence leads to scarce experience in solving this kind of situation. There are some risk factors or mechanism as an underlying etiology of uterine inversion. The authors concluded that the presence of myoma geburt can be assosiated with the chronic uterine inversion. Surgical approach by eksterpation of myoma geburt with total hysterectomy can be the right procedure. Therefore, it is essential to keep in mind this diagnosis in all cases of vaginal bleeding. Keywords: uterine inversion; myoma geburt